1983
DOI: 10.1254/jjp.33.593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geranylgeranylacetone on aspirin-induced changes in gastric glycoproteins.

Abstract: Abstract-The effects of aspirin and treatment with geranylgeranylacetone (GGA), an antiulcer drug, on the content of gastric glycoproteins were investigated in pylorus ligated rats. In normal rats, the amount of gastric glycoproteins in the mucous layer was about 1.5 times higher than that in the gastric mucosa, indicating that the glycoproteins were distributed in the mucous layer as a highly concentrated state. Aspirin (100 mg/kg, p.o.) decreased the content of gastric glycoproteins both in the mucous layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Previous stud ies on its action on the gastric mucosa showed that TPA mitigated the reduction in mucosal blood flow in restrained water im mersion stress [7], preventing the decrease in gastric glycoproteins [25] and stimulating endogenous bicarbonate secretion [26], The administration of TPA in the present study inhibited decreases in EC values. In this connection, when gastric mucosal injury is induced by hydrochloric acid, the conver sion of ATP to ADP by ATPase is increased and the conversion of ATP to cAMP by ade nylate cyclase diminishes, while prostacy clins, which have a mucosal protective ef fect, enhance both of these transformations and therefore cause a drop in the ATP/ADP ratio as well as in the value of the EC [27], On the other hand, cimetidine confers cytoprotection by retarding both of these trans formations and thereby inhibits decreases in the ATP/ADP ratio and the EC.…”
Section: Discussionsupporting
confidence: 51%
“…Previous stud ies on its action on the gastric mucosa showed that TPA mitigated the reduction in mucosal blood flow in restrained water im mersion stress [7], preventing the decrease in gastric glycoproteins [25] and stimulating endogenous bicarbonate secretion [26], The administration of TPA in the present study inhibited decreases in EC values. In this connection, when gastric mucosal injury is induced by hydrochloric acid, the conver sion of ATP to ADP by ATPase is increased and the conversion of ATP to cAMP by ade nylate cyclase diminishes, while prostacy clins, which have a mucosal protective ef fect, enhance both of these transformations and therefore cause a drop in the ATP/ADP ratio as well as in the value of the EC [27], On the other hand, cimetidine confers cytoprotection by retarding both of these trans formations and thereby inhibits decreases in the ATP/ADP ratio and the EC.…”
Section: Discussionsupporting
confidence: 51%
“…There have been numerous reports indicating that GGA exerts its mucoprotective effects through the induction of HSP and the stimulation of mucin secretion in the gastric mucosa [9,10,11,24,25,26]. GGA is an acyclic polyisoprenoid compound that protects against gastric injury induced by cold or water-immersion restraint stresses, and by non-steroidal anti-inflammatory drugs [10,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Geranylgeranylacetone (GGA) is a mucoprotective drug developed in Japan that has been shown to not only induce mucous secretion in the stomach, but to also upregulate heat shock proteins (HSPs) in gastric epithelial cells [11,12,13,14]. GGA is now widely used to treat patients with gastric ulcers or chronic gastritis regardless of H. pylori infection, both in Japan and other Asian countries [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty minutes later, all rats were given intragastrically 1 ml o f absolute ethanol and after 30 min the animals were killed by decapitation and their stomachs removed. The dose of GGA used in the experiments was chosen based on earlier stud ies which demonstrated that GGA at 200 mg/kg was most effective in the prevention of gastric mucosal damage in rats [12,15,16].…”
Section: Animal Preparationmentioning
confidence: 99%